Best Practices in the Clinical Management of Progressive Supranuclear Palsy and Corticobasal Syndrome: A Consensus Statement of the CurePSP Centers of Care - Bluett, Brent; Pantelyat, Alexander Y.; Litvan, Irene; Ali, Farwa; Apetauerova, Diana; Bega, Danny; Bloom, Lisa; Bower, James; Boxer, Adam L.; Dale, Marian L.; Dhall, Rohit; Duquette, Antoine; et al. (Frontiers in Neurology, 2021)
Progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS; the most common phenotype of corticobasal degeneration) are tauopathies with a relentless course, usually starting in the mid-60s and leading to death after an average of 7 years. There is as yet no specific or disease-modifying treatment. Clinical deficits in PSP are numerous, involve the entire neuraxis, and present as several discrete phenotypes. They center on rigidity, bradykinesia, postural instability, gait freezing, supranuclear ocular motor impairment, dysarthria, dysphagia, incontinence, sleep disorders, frontal cognitive dysfunction and a variety of behavioral changes. CBS presents with prominent and usually asymmetric dystonia, apraxia, myoclonus, pyramidal signs and cortical sensory loss. The symptoms and deficits of PSP and CBS are amenable to a variety of treatment strategies but most physicians, including many neurologists, are reluctant to care for patients with these conditions because of unfamiliarity with their multiplicity of interacting symptoms and deficits. CurePSP, the organization devoted to support, research and education for PSP and CBS, created its CurePSP Centers of Care network in North America in 2017 to improve patient access to clinical expertise and develop collaborations. The directors of the 25 centers have created this consensus document outlining best practices in the management of PSP and CBS. They formed a writing committee for each of 12 sub-topics. A 4-member Steering Committee collated and edited the contributions. The result was returned to the entire cohort of authors for further comments, which were considered for incorporation by the Steering Committee. The authors hope that this publication will serve as a convenient guide for all clinicians caring for patients with PSP and CBS and that it will improve care for patients with these devastating but manageable disorders.